2013
DOI: 10.1016/j.ajog.2013.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Maternal engineered nanomaterial exposure and fetal microvascular function: does the Barker hypothesis apply?

Abstract: Objective-The continued development and use of engineered nanomaterials (ENM) has given rise to concerns over the potential for human health effects. While the understanding of cardiovascular ENM toxicity is improving, one of the most complex and acutely demanding "special" circulations is the enhanced maternal system to support fetal development. The "Barker Hypothesis" proposes that fetal development within a hostile gestational environment may predispose/program future sensitivity. Therefore, the objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(105 citation statements)
references
References 42 publications
(54 reference statements)
9
95
1
Order By: Relevance
“…The Sumner et al study also reported differences in the distribution pattern of radiolabelled C60 between pregnant and non-pregnant life stages [22], which is presumed to be due to changes in vascular reactivity of various vascular beds during pregnancy. The distribution kinetics of nanoparticles can influence both maternal and fetal vascular function [25], embryogenesis, cellular signalling, inflammation, cell cycle, lipid metabolism [26] fetal growth and malformations [23]. The effects of C60 exposure on maternal/fetal vascular reactivity have not been extensively investigated despite the possibility of occupational, general environmental and therapeutic/diagnostic exposures during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The Sumner et al study also reported differences in the distribution pattern of radiolabelled C60 between pregnant and non-pregnant life stages [22], which is presumed to be due to changes in vascular reactivity of various vascular beds during pregnancy. The distribution kinetics of nanoparticles can influence both maternal and fetal vascular function [25], embryogenesis, cellular signalling, inflammation, cell cycle, lipid metabolism [26] fetal growth and malformations [23]. The effects of C60 exposure on maternal/fetal vascular reactivity have not been extensively investigated despite the possibility of occupational, general environmental and therapeutic/diagnostic exposures during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, fetal microvessel dysfunction following exposure to engineered nanomaterials which was recently proposed by Stapleton et al [11] may be a possible underlying explanation for our observations of reduced fetal weight despite the absence of augmented contractile responses in umbilical circulation. Stapleton et al [11] used the fetal tail artery as a representative vessel from the fetal microcirculation and reported decreased responses in both endothelium dependent and independent relaxation [60]. Their findings suggests the applicability of the Barker Hypothesis ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggests the applicability of the Barker Hypothesis ( i.e. the relation between retarded growth in early life and risk of adult disease is due to long term effects on physiology and metabolism imposed by an adverse environment during critical periods of development) to explain the changes observed in the fetus following maternal nanoparticle exposure [60,61]. This hypothesis may also hold true for our MWCNT exposure scenario, suggesting that the differences in the fetal weight gain may be a reflection of limited blood supply due to increased contraction observed in the uterine vascular segments.…”
Section: Discussionmentioning
confidence: 99%
“…Together with a lack of response to nitric oxide, these findings indicate that exposure compromised the normal microvascular dilation in fetal vasculature [141]. Further studies demonstrated that microvascular dysfunction coincided with a reduction in the maximal mitochondrial respiration in both cardiac and uterine tissues [142].…”
Section: Cardiovascular Systemmentioning
confidence: 96%